Physics Learning With Entrepreneurship Basis By Applying Project-Based Learning Methods In Dynamic Fluid Materials - Trisnawati, Ida; Sunarti, Titin; Zainuddin, Abu (Jurnal Penelitian Pendidikan Fisika, 2021)
This study aims to determine the understanding of the concept of dynamic fluid material in physics subjects, the ability to compile a simple business plan through the project-based learning method, and to find out the learning interests of class XI IPS 1 students with a special interest in Physics at SMA Lab School Unesa 2020/2021 academic year. This research uses descriptive quantitative method. Data collection was carried out by means of test methods, simple business plan assignments, and questionnaires to students. Students are given tests by working on questions and assigning a simple business plan as a simple project. To find out students' interest in learning, a questionnaire was filled out via google form and interviews. The results showed that: (1) The level of conceptual understanding of the dynamic fluid material of the students reached 2.14 indicating the medium category (2) the ability level of students to make simple business plans reached 3 indicating the category began to develop and (3) the level of student interest in learning reached 75,19 indicates good category. So the application of entrepreneurship-based physics learning using the project-based learning method is quite good for IPS students in order to foster understanding of the concept of dynamic fluid material, making simple business plans, and interest in learning physics.